Students’ Perspective toward National Examination in Indonesia - Weni Ratnasari (STAI Auliaurrasyidin Tembilahan, 2018)
National exam is one of big issues in Indonesian Educational system. Major controversies occur in implementing the national examination. As a state mandatory exam that every student has to participate, it determines whether a student deserves to graduate or must stay. The policy makers believe if such condition is applied, teachers will be pushed to teach better and students will be motivated to learn more. However, some research revealed negative impacts along the release of such policy. It sparks negative impacts that policy makers should be aware. This article discusses students’ perspective regarding the benefits and drawbacks of National exam, and solution for better implementation of National Examination in Indonesia.